2005
DOI: 10.1093/rheumatology/keh672
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of autoantibodies to human muscarinic acetylcholine receptor 3213–228 in primary Sjögren's syndrome

Abstract: The presence of m3AChR(213-228) antibodies is a common feature in pSS. Although it is significantly more common in pSS than in the comparison groups, anti-m3AChR(213-228) positivity is not exclusive to pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 17 publications
3
57
1
Order By: Relevance
“…Naito et al found that altered peptides derived from the second extracellular domain of M3R inhibited IFN-γ production by suppressing the number of IFN-γ-producing T cells in patients with SS [42]. A finding was also reported that leucopenia, a common extra-glandular manifestation seen in SS patients, was significantly more common in anti-M3R 213-228 positive pSS patients (53%) than in those without this antibody (14%) [21]. In an aforementioned report [26], anti-M3R 205-220 positivity was associated with hematological abnormalities, such as leucopenia, anemia, and thrombocytopenia in pSS.…”
Section: Pathogenic Involvement Of Anti-m3r Autoantibodies In Ssmentioning
confidence: 94%
See 3 more Smart Citations
“…Naito et al found that altered peptides derived from the second extracellular domain of M3R inhibited IFN-γ production by suppressing the number of IFN-γ-producing T cells in patients with SS [42]. A finding was also reported that leucopenia, a common extra-glandular manifestation seen in SS patients, was significantly more common in anti-M3R 213-228 positive pSS patients (53%) than in those without this antibody (14%) [21]. In an aforementioned report [26], anti-M3R 205-220 positivity was associated with hematological abnormalities, such as leucopenia, anemia, and thrombocytopenia in pSS.…”
Section: Pathogenic Involvement Of Anti-m3r Autoantibodies In Ssmentioning
confidence: 94%
“…However, the variation in the sensitivity was quite large, ranging from 0% to 97% (Table 1). Naito et al [25] observed only 11/122 (9%) anti-M3R positivity in pSS patients using the M3R 213-237 peptide, while Kovács et al [21] found that 66 out of 73 (90%) pSS patients were anti-M3R 213-228 -positive, using a peptide-GST fusion protein. He et al [26] demonstrated that the sensitivity (62.2%) and specificity (95.1%) of the cyclic M3R 205-220 peptide were higher than that of the linear peptide (56.1% and 84.7%, respectively).…”
Section: The Prevalence Of Anti-m3r Autoantibodies In Patients With Pssmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular; antibodies to the antigens SS-A/Ro and SS-B/ La are commonly used in the diagnosis of pSS [2]. The presence of subtypes M 1 [3], M 3 [4,5] and M 4 [6] specific autoantibodies in 83% -90% persons with pSS [7] is an important advance towards understanding the pathogenesis of pSS not only in terms of impaired glandular function, but also because of peripheral parasympathetic dysfunction associated with the disease [8,9].…”
Section: Introductionmentioning
confidence: 99%